Electrospun Polymers in Cartilage Engineering—State of Play - Yilmaz, Elif Nur; Zeugolis, Dimitrios I. (Frontiers in Bioengineering and Biotechnology, 2020)
Articular cartilage defects remain a clinical challenge. Articular cartilage defects progress to osteoarthritis, which negatively (e.g. remarkable pain, decreased mobility, distress) affects millions of people worldwide and is associated with excessive healthcare costs. Surgical procedures and cell-based therapies have failed to deliver a functional therapy. To this end, tissue engineering therapies provide a promise to deliver a functional cartilage substitute. Among the various scaffold fabrication technologies available, electrospinning is continuously gaining pace, as it can produce nano- to micro- fibrous scaffolds that imitate architectural features of native extracellular matrix supramolecular assemblies and can deliver variable cell populations and bioactive molecules. Herein, we comprehensively review advancements and shortfalls of various electrospun scaffolds in cartilage engineering.